Supervision Experiences of School Counselors-in-Training: An Interpretative Phenomenological Study - Anita Pool; Kristen N Dickens; Matthew Lyons; Barbara Herlihy (Teaching and Supervision in Counseling, 2021)
School counselors-in-training receive university and site supervision during their field experiences. University supervision may be provided by a faculty member or doctoral student who lacks school counseling experience. School counselors as site supervisors may not be trained to supervise. Further, the multiple systems may have differing expectations for supervisees. Interpretative Phenomenological Analysis was used to explore the lived experiences of eight master’s level school counselors-in-training with supervision. The four super-ordinate themes included: impact of counselor education program, supervisor characteristics, significance of feedback, and characteristics of the supervisee. Findings suggested programmatic changes counselor educators can make to strengthen student preparation.
Keywords: supervision; school counselors-in-training; school counseling